Posebne pravice Romske skupnosti - privilegij manjšine ali mednarodna obveznost večine - Klopčič, Vera (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2005)
The author discusses certain characteristics of the status of Roma in international documents and legislation of individual states with regard to definitions, legal status and special measures aimed at protection of Roma community.Particularly important among the questions concerning different approaches to the protection of Roma is the discussion on positive discrimination of Roma in the field of improvement of their unfavourable social status, as well as special measures for the elimination of prejudice and racial hatred. In conformity with the Recommendation of the Parliamentary Assembly of the Council of Europe no. 1557 from 2002 concerning the legal status of Roma in some European states, the author strives for Roma to be acknowledged the status of national minority in every state they inhabit, and to be given individual and collective minority rights. The article focuses on the stipulations of two special laws on minority protection, adopted in Serbiaand Montenegro (2002) and Poland (2005). Having been subject to unfavourable historical situation and negative attitudes on the part of majority populations, Roma continue to live in unfavourable social conditions and are still victims of marginalization and prejudice. That is why the documents treat them as a threatened/vulnerable community which has to be given the chance of social integration. In 2004 legal experts in EU even proposed a special Directive on social integration of Roma. The question is whether legal treatment of Roma as a socially vulnerable community offers sufficient basis for the implementation of this goal, because it might be just another pragmatic solution which fails to deal with the essential developmental issues and does not try to alter the relations of power within the existing political structures.
Keywords: Romi; Cigani; etnične skupine; pravice manjšin; Europe; Evropa; družbena integracija; pravno varstvo manjšin